1992
DOI: 10.1073/pnas.89.14.6265
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human immunodeficiency virus activity by phosphorodithioate oligodeoxycytidine.

Abstract: Phosphorothioate oligodeoxynucleotides exert a sequence-independent cytoprotective effect against human immunodeficiency virus type 1 (HIV-1). We now report that phosphorodithioate-containing oligodeoxycytidines are very potent inhibitors of HIV-1 reverse transcriptase in vitro, as they exhibit an increasing inhibitory effect with length and number of phosphorodithioate internucleotide linkages. This inhibitory effect can be at least 30-fold greater with phosphorodithioate oligodeoxycytidine than for the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…It has been reported that S-oligos with a chain length longer than 15 could bind and inhibit the proteins, and that the inhibitory effect reached a plateau level with a chain length of 28 (Gao et al, 1992;Marshall et al, 1992). In the present study, we reported that the inhibitory effect of S-oligos on DNA-PK activity is sequence-independent and is dependent on the chain length.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…It has been reported that S-oligos with a chain length longer than 15 could bind and inhibit the proteins, and that the inhibitory effect reached a plateau level with a chain length of 28 (Gao et al, 1992;Marshall et al, 1992). In the present study, we reported that the inhibitory effect of S-oligos on DNA-PK activity is sequence-independent and is dependent on the chain length.…”
Section: Discussionsupporting
confidence: 62%
“…The inhibitory effect reached a plateau level with a chain length of 36, which is almost the same length as previously reported. Marshall et al (1992) reported that the inhibitory effect of oligonucleotides on HIV-1 reverse transcriptase could be at least 30-fold greater with phosphorodithioate oligonucleotides, which have two sulphur at each site of internucleotide linkages, than with phosphorothioate oligonucleotides. Benimetskaya et al (1995) reported that binding of phosphorothioate oligonucleotides to proteins is independent on P-chirality at the internucleotide linkage sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These suggested mechanisms include blocking of viral adsorption (Luganini et al, 2008;Wyatt et al, 1994) and/or inhibition of HIV-1-specific enzymes, such as reverse transcriptase (Marshall and Caruthers, 1993;Marshall et al, 1992) or integrase (Jing and Hogan, 1998;Jing et al, 2000). P = S oligodeoxycytidine [poly (SdC) 28 ] interacts specifically with the positively-charged V3 loop of HIV-1 gp120 (Vaillant et al, 2006), possibly resulting in the inhibition of HIV-1 replication.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms suggested have included adsorption blocking (9,16,47,50,51,53) and inhibition of HIV-1-specific enzymes, such as reverse transcriptase (29)(30)(31) or integrase (21-23, 36, 42). However, most studies of the antiviral mechanisms of PAS ONs, as well as recent studies with small interfering RNA (siRNA) against HIV-1 (3,5,7,35,38,39,49), have been conducted by transfection or viral vector-mediated delivery (4,17,27,33,34), rather than simple treatment of the infected culture.…”
mentioning
confidence: 99%